Findings on Student Use of Social Media at the Collegiate, Undergraduate, and Graduate Levels: Implications for Post-Secondary Educators - Nagel, Tyler; Remillard, Chaseten; Aucoin, Robert; Takenishi, Akari (Journal of University Teaching and Learning Practice, 2018)
In this paper, we present findings on social media use by students at two institutions in three levels of post-secondary programs. We find that students are almost universally using at least one social network, with Facebook as the most popular, and Instagram second. Many respondents are simultaneously active on several social networks. However, few post to any social medium more than once per day. Social media usage levels of students in our survey far exceeded that of the adult Canadian population at large. Changes in student posting habits during the course varied widely with the level of post-secondary program, as did views on the professional applications of social media.